2016
DOI: 10.1002/ente.201500368
|View full text |Cite
|
Sign up to set email alerts
|

A Thermally Stable, Combustion‐Resistant, and Highly Ion‐Conductive Separator for Lithium‐Ion Batteries Based on Electrospun Fiber Mats of Crosslinked Polybenzoxazine

Abstract: Porous and thermally stable membranes are attractive materials as separators in lithium‐ion batteries. This work reports a new class of high‐performance separators for Li‐ion batteries based on a crosslinked polybenzoxazine electrospun fiber mat (CR‐PBz‐FbM). The CR‐PBz‐FbM separator shows a high ion conductivity of 2.92 mS cm−1 (5.2 times the value recorded for Celgard 2300), a low MacMullin number of 3.35, ultrahigh electrolyte uptake (≈825 %), and near‐zero shrinkage at 150 °C. Consequently, the CR‐PBz‐FbM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 50 publications
(132 reference statements)
0
17
0
Order By: Relevance
“…The benzoxazine rings and corresponding cross-linked benzoxazine polymers possess tertiary amine groups, which have the ability to coordinate with Li + ions and facilitate Li + ion transportation. , Chirachanchai et al reported that benzoxazine compounds could interact with alkali ions and are suitable for application in ion extraction . Our previous work also demonstrated that cross-linked PBz-based electrospun membranes show a high liquid electrolyte compatibility and ionic conductivity . Therefore, in this work, a cross-linkable polybenzoxazine possessing PEO segments (PEO-PBz) has been prepared for application in SPEs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benzoxazine rings and corresponding cross-linked benzoxazine polymers possess tertiary amine groups, which have the ability to coordinate with Li + ions and facilitate Li + ion transportation. , Chirachanchai et al reported that benzoxazine compounds could interact with alkali ions and are suitable for application in ion extraction . Our previous work also demonstrated that cross-linked PBz-based electrospun membranes show a high liquid electrolyte compatibility and ionic conductivity . Therefore, in this work, a cross-linkable polybenzoxazine possessing PEO segments (PEO-PBz) has been prepared for application in SPEs.…”
Section: Introductionmentioning
confidence: 99%
“…41 Our previous work also demonstrated that cross-linked PBz-based electrospun membranes show a high liquid electrolyte compatibility and ionic conductivity. 42 Therefore, in this work, a cross-linkable polybenzoxazine possessing PEO segments (PEO-PBz) has been prepared for application in SPEs. The cross-linked PEO-PBz (CR-PEO-PBz) has been utilized as a binder for preparation of the electrode for Li-ion batteries.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lithium-ion batteries (LIBs) receive continuous attention with focus on addressing some of the critical concerns in current systems, such as safety issues, charging–discharging performance, and cost . One attractive field of study is seeking suitable electrolytes to replace the conventional porous-polyolefin-based separators impregnated with liquid electrolytes, which might cause fire hazards and serious safety problems due to the loss of separating functions of the separators between the cathode and the anode at high temperatures. , Although thermally stable , separators have been reported to overcome this problem, another solution could be employing solid polymer electrolytes (SPEs). In addition to addressing the safety problems caused by separator shrinkage/deformation, SPEs might exhibit some advantages of flame retardancy and suppression of dendritic lithium growth. Nevertheless, SPEs still have some flaws such as relatively low ion conductivities and poor compatibility with electrodes. , Efforts to resolve these issues are continuously reported. …”
Section: Introductionmentioning
confidence: 99%
“…Electrospun polyimide nonwoven membranes are thermally stable at 500 °C . A cross‐linked polybenzoxazine electrospun fiber mat shows near‐zero thermal shrinkage at 150 °C . Poly(vinylidene fluoride) (PVdF)/SiO 2 composite nonwoven membranes are also thermally stable at a high temperature of 400 °C .…”
Section: Introductionmentioning
confidence: 99%